Impact of Child Birth Order on Dental Caries and Anxiety Level - Abeer A. Yahya (Al-SalamJournal for Medical Science)
Background: Many factors influence dental caries as well as dental anxiety of paediatric children, one of them is child-birth order. Child’s growth and development greatly influenced by the surrounding environment which may has positive or negative impact on his physical, mental and even emotional health. This study was conducting to evaluate whether child birth-order has an influence on dental caries and dental anxiety of children attending pediatric dental clinic. Materials and methods: this study conducted at pediatric dental clinic/ Ibn Sina University of Medical and Pharmaceutical Sciences, (112) pediatric patients included in this study and grouped according to their birth order as eldest group (N=37), middle group (N=35) and youngest group (N=40). For each group both dental caries using (DMFS/dmfs index) and dental anxiety using (faces version of the modified child dental anxiety scale MCDAS (f)) were measured. One-way ANOVA test used for statistical analysis. Results: Data showed significant impact for birth order on dental caries with (p= 0.035), while the study found non-significant difference between child-birth order and dental anxiety with (p= 0.899). Conclusion: child birth-order significantly influence dental caries with eldest children less affected by dental caries compared to youngest children, with non-significant impact on dental anxiety.